2011
DOI: 10.1016/j.mri.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of regional left ventricular endocardial curvature from cardiac magnetic resonance images

Abstract: Purpose: Left ventricular (LV) remodeling is usually assessed using global changes in LV volume. We hypothesized that threedimensional analysis of regional endocardial curvature from magnetic resonance images could provide clinically useful information on localized LV remodeling. We tested this approach by investigating regional differences in endocardial curvature in normal and hypokinetic ventricles. Materials and Methods: Images were obtained in 44 patients with normal LV function (NL, N=14), dilated cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This approach has been previously used in the context of 3D analysis of cardiac magnetic resonance images (22). To achieve this, a quadratic polynomial function was fit to the local neighborhood of each point belonging to the LV endocardial surface.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been previously used in the context of 3D analysis of cardiac magnetic resonance images (22). To achieve this, a quadratic polynomial function was fit to the local neighborhood of each point belonging to the LV endocardial surface.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have demonstrated the potential use of 3D shape analysis to obtain not only new global indices, such as sphericity and conicity, 21 but also regional shape indices, such as 3D curvature. [22][23][24] Having access to these parameters on a frame-by-frame basis from 3DE images without extensive user interaction and time commitment is likely to prove clinically useful from both diagnostic and prognostic points of view. 25,26 Harnessing this information for potential clinical use may prove beneficial in future studies designed to investigate this aspect of cardiac chamber shape in different disease states.…”
Section: Future Directionsmentioning
confidence: 99%
“…Echocardiography and cardiac magnetic resonance imaging (MRI) have permitted valuable clinical contributions to the non-invasive diagnosis of cardiac dysfunctions based on myocardial deformation (Claus et al, 2015). However, every heart is different and the variability in geometry and local curvature of the left ventricle (LV) entails different amplitude and timing of regional motion (Bogaert and Rademakers, 2001;Maffessanti et al, 2011). Different normal patterns of LV regional deformation allow a natural synchrony, which does not mean simultaneity, able to create the proper intraventricular pressure gradients (IVPGs) that drive blood motion during both ventricular ejection and ventricular filling.…”
Section: Introductionmentioning
confidence: 99%